Nursing Care Systems: Enhancing Care Processes in Practice and Management - Marin, H.F.; Carr, R. (Yearbook of Medical Informatics, 2008)
ObjectiveTo summarize aspects of nursing informatics application and introduces challenges that are currently being addressed by nurses around the world.MethodsKey contributions in the field are surveyed and put in the perspective of the IMIA Nursing Informatics Strategic Plan.Results As a discipline, nursing informatics offers real and practical instruments and opportunities to delivery nursing care across settings, units of care and specialties. A variety of patient care systems are managed by nurses who are introduced to this link during their training embracing information networks, communication skills together with an ability to work both in practice and administrative positions in a variety of clinical and community settings.Conclusion At a time when the tendency is toward a computer-based patient record, nurses must be able to identify what kind of nursing data and information will construct useable and useful nursing knowledge. There are many options for each area of application and the selection must be done carefully, considering the enhancement for organizational, technological and local requirements.
Keywords: Nursing; informatics; information; communication; technology